A High Five for ChemistryOpen. Issue 1 (3rd February 2016) - Peralta, David; Ortúzar, Natalia
Abstract : Fabulous at five ! When ChemistryOpen was launched in 2011, it was the first society‐owned general chemistry journal to publish open‐access articles exclusively. Five years down the line, it has featured excellent work in all fields of chemistry, leading to an impressive first full impact factor of 3.25. In this Editorial, read about how ChemistryOpen has grown over the past five years and made its mark as a high‐quality open‐access journal with impact.